Indirect autonomic nervous system activity assessment in patients with myocardial infarction. (26th April 2021) - Aleksandrenko, VA; Kuzheleva, EA; Garganeeva, AA
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Abnormalities in the cardiac sympathetic nervous system have been documented in myocardial infarction (MI) and have been directly implicated in pathogenesis and progression of MI. Assessment of the autonomic nervous system activity in acute stage of MI allowed us to identify groups of high-risk patients. Purpose: To investigate the sympathetic nervous system activity in patients with MI by assessing the condition of beta-adrenergic reactivity of erythrocytes. To analyze ADRB1 Arg389Gly associations with the state of beta-adrenergic reactivity of erythrocytes in patients with MI. Methods: During the study period, 62 patients were enrolled. The patients were divided into 2 groups. The first group consisted of 11 patients (nine women and two men, median age of 54.0 [49.0;61.0] years) with normal beta-adrenergic reactivity of erythrocytes, the second group consisted of 51 patients (40 women and 11 man, median age of 61.0 [48.0;72.0] years) with abnormal beta-adrenergic reactivity of  erythrocytes. The research of beta-adrenergic reactivity of erythrocytes was conducted by analysis of changing erythrocyte osmoresistance under the influence of beta blocker in the first 6 hours from the onset of the heart attack. The genetic research was conducted by PСR method in real time. Results: Groups of patients were comparable in main clinical indicators (anamnesis of ischemic heart disease and chronic heart failure, frequency of beta blockers administration before and during of MI, electrocardiography features: elevation of ST-segment, Q-wave and etc.). The second group presented with a higher occurrence of acute left ventricular failure (33.3% vs 0%, p = 0.026) and arterial hypertension (90.2% vs 63.6%, p = 0.044). Parameters of myocardial damage were significantly higher in the second group than the first group. Primarily, this manifested in the presence of a greater number of hypokinesis zones on echocardiography (p = 0.015). In addition, patients of the second group had a lower ejection fraction according to echocardiography (51.0 [46.5;59.0]% vs 58.0 [52.0;63.0]%, p = 0.042). Levels of blood necrosis biomarkers were significantly higher in the second group, e.g. Troponin I (24.1 [9.9;68.0] ng/ml vs 1.3 [0.2;1.8] ng/ml, p = 0.001). At the same time statistically significant distinctions of the severity of coronary atherosclerosis in groups were not revealed. The analysis of ADRB1 Arg389Gly demonstrated association of CC-genotype with abnormal beta-adrenergic reactivity of erythrocytes [OR 5.9, 95% СI 1.16-30.25, p = 0.043]. Conclusion: Patients with an abnormal beta-adrenergic reactivity were characterized by a greater volume of damage to the heart muscle. Moreover, association of CC-genotype of gene ADRB1 Arg389Gly with abnormal beta-adrenergic reactivity of erythrocytes was identified.